Mycotoxins—Biomonitoring and Human Exposure - Kristina Habschied; Gabriella Kanižai Šarić; Vinko Krstanović; Krešimir Mastanjević (Toxins, 2021)
Mycotoxins are secondary metabolites produced by fungal species that commonly have a toxic effect on human and animal health. Different foodstuff can be contaminated and are considered the major source of human exposure to mycotoxins, but occupational and environmental exposure can also significantly contribute to this problem. This review aims to provide a short overview of the occurrence of toxigenic fungi and regulated mycotoxins in foods and workplaces, following the current literature and data presented in scientific papers. Biomonitoring of mycotoxins in plasma, serum, urine, and blood samples has become a common method for determining the exposure to different mycotoxins. Novel techniques are more and more precise and accurate and are aiming toward the simultaneous determination of multiple mycotoxins in one analysis. Application of liquid chromatography (LC) methodologies, coupled with tandem mass spectrometry (MS/MS) or high-resolution mass spectrometry (HRMS) has become a common and most reliable method for determining the exposure to mycotoxins. Numerous references confirm the importance of mycotoxin biomonitoring to assess the exposure for humans and animals. The objectives of this paper were to review the general approaches to biomonitoring of different mycotoxins and the occurrence of toxigenic fungi and their mycotoxins, using recent literature sources.